MANAGEMENT PHYSIOTHERAPY FOR MYALGIA UPPER TRAPEZIUS CASE SITTING FOR A LONG TIME WORKING IN FRONT OF A LAPTOP DURING WORK FROM HOME: CASE REPORT - Pradipta, Alvian Willy; Perdana, Suryo Saputra; Debbita, Nurraya Martha (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Work from Home during the pandemic covid-19 made almost all Indonesian students online learning activities at home. The use of laptops in a sitting position for too long causes Myalgia Upper Trapezius in students. A study says complaints of 86.4% in the neck and 76.2% in the shoulders during WFH. The purpose of writing is to find out the benefits of Short- Wave Diathermy, Myofascial Release and Stretching to reduce pain and increase joint range of motion. Case Presentation: The patient used was a female student with complaints of pain and limitation of motion in the neck area and was chronic. Pain is caused by a static position sitting in front of the laptop for too long, causing limited neck movement during WFH. Management and Outcome: Short Wave Diathermy, Myofascial Release and Stretching can reduce pain intensity and increase joint range of motion in women with Myalgia Upper Trapezius. Discussion: After 3 weeks physiotherapy, the results were evaluated 3 times. Get the results of reducing silent pain with VAS evaluation 1: 4.5 evaluation 3: 1.1 tenderness evaluation 1: 5.1 evaluation 3: 2.1 and motion pain evaluation 1: 5.3 evaluation 3: 2.5. An increase in the range of motion neck of the joint also occurs in movement with Goniometer, Flexion evaluation 1: 260 evaluation 3: 380, Extension evaluation 1: 300 evaluation 3: 450, Side right flexion evaluation 1: 380 evaluation 3: 440, Side left flexion evaluation 1: 200 evaluation 3: 440, Right rotation evaluation 1: 400 evaluation 3: 480, Left rotation evaluation 1: 300 evaluation 3: 470. Application of Short-Wave Diathermy, Myofascial Release and Stretching can reduce pain and increase the range of motion of joints in patients with Upper Trapezius Myalgia. Conclusion: Physiotherapy management in the Myalgia Upper Trapezius after carrying out the program for 3 weeks with the intensity of 3 times the threat in 1 week reduce pain and increase ring of motion. Ergonomic position and consistency patient during physiotherapy with SWD, Myofascial release and stretching is very helpful in-patient recovery.